Victory Milestones. Aleksander Alekseyevich Vybornov Turns 70 - Oleg D. Mochalov (Археология евразийских степей, 2025)
The article is devoted to the achievements of the famous archaeologist A.A. Vybornov, who turns 70 this year. The researcher has been working at Samara State University of Social Sciences and Education for 45 years. He is the head of the university's scientific school. He studied a significant number of archaeological sites of the Mesolithic, Neolithic, and Chalcolithic eras in the Volga-Urals and Kama region. Under his leadership, 10 candidate dissertations were defended. A.A. Vybornov is the author of more than 400 scientific and educational works. His scientific, scientific-organizational and teaching activities are analyzed. The article is important for the history of archaeology in Russia.